MODIFICATION OF A CENTRIFUGE BOTTOM BEARING IN ORDER TO RAISE ITS MEAN TIME BETWEEN FAILURES (MTBF) - KESUMA (NIM : 13104089); Pembimbing Utama : Prof. Dr. Indra Nurhadi, HARDY
Centrifuge is a device in a processing industry used to reduce water content of the terephthalic acid by means of centrifugal force. To generate the centrifugal force in the centrifuge which is the focus of this report, centrifuge has several rotating component in it which are supported by angular contact ball bearing and cylindrical roller bearing. According to the operational records of 10 years, it is considered that these bearings’ lifetime is too short so that the maintenance cost is too much. In this report, the application of journal and axial sliding bearing to replace those rolling element bearings is examined. This examination includes bearing geometry determination, bearing material selection, fit calculations which control how those components are assembled and tribology analysis to predict bearing characteristics, lubricant characteristics, and also dissipated power of bearing theoretically. Moreover, Examination is also done for some complementary components such as springs and O-ring. Helical springs which are assembled in parallel is designed to replace two original Belleville springs in serial configuration. While, standard O-ring dimension along with the material is chosen to replace labyrinth seal of the original design. As the result, the modification is proven to has risen the centrifuge bottom bearing’s productive lifetime while enable the re-application of the original bearing. The product which has been tested in the actual environment and condition since 21 April 2008 until the time this report is written, is still operating in good condition.